Sobre el derecho constitucional (un análisis de la dogmática y de las cátedras) - Dolabjian, Diego A. (2015)
This paper proposes an approach to Constitutional Law starting from the analysis of the academic development of the subject in Argentina with special focus on the chairs of the School of Law of the University of Buenos Aires (UBA). Thus, basically, the aim is to provide a basic guide of our Constitutional Law, that may become useful for both students that face the study of the subject in the UBA and for the entire academic community in general.